The censoring of accessibility: am I free to be impaired? - Martins, Cláudia (2022)
Being disabled/ impaired has been a reason for exclusion from family life but mostly from society since times immemorial. The demonological model of disability (Aguado Diaz, 1995; Amiralian et al., 2000; Oliveira, 2000) argues that people with disabilities (PwD) were regarded as the embodiment of evil or of a divine punishment and, because of this, were either segregated from social life or eliminated altogether, for instance, by chocking or drowning. However, there are accounts of these people being used for freak shows and circuses. From the Middle Ages onwards, the focus shifted to the medical-clinical approach that concerned itself with identifying and attempting to solve the medical causes behind disabilities. This led to the creation of the first asylums and specialised hospitals, such as the Bethlem Royal Hospital, in London in 1247, and, in 1260, the asylum of Quinze-Vingts, in Paris, founded by Louis XIII for blind people. Only after the 2nd WW and the 1990s would this mindset begin to change: after the former, stemming from the waves of demands voiced by the soldiers returning from the war with multiple disabilities, seeking to be reintegrated in and valued by the society that had exploited them, and the latter that crowned the concept of inclusion, placing the onus for the barriers in PwD’s lives on society itself. Thus, impairment would become a keyword as the functional difficulties people may have and disability as the obstacles society creates – in its ableist (Nario-Redmond, 2020) overall approach – by not being prepared for all sorts of people. Despite all this evolution, am I free to be different? Can I be accepted in my society if I have a disability/ impairment? Will I be allowed to fit in? Will I be eyed as an uncomfortable burden that politically correctness forces others to accept? How educated are we in embracing the diversity in people’s abilities and in freeing ourselves from the long-held belief in “normality”? These are some of the questions I aim to reflect upon and, drawing on thought-provoking examples, lead to the deconstruction of the traditional assumptions on disability/ impairment.